Contribution of the Semiological Approach to Deixis–Anaphora in Sign Language: The Key Role of Eye-Gaze - Garcia, Brigitte; Sallandre, Marie-Anne (Frontiers in Psychology, 2020)
We address the issue of deixis-anaphora in sign language (SL) discourse from a cross-linguistic and typological perspective, focusing on the key role of both interlocutors' gaze as the basis of deixis in these languages. According to our theoretical framework, the Semiological Approach, SL structuring stem from a maximum exploitation of the visuo-gestural modality, which result in two main modes of meaning production, depending on the signer's semiotic intent. Involving equally both non-manual and manual parameters, the first mode, expressing the intent to say while showing, uses constructions based on structures, the termed “transfer structures”. The second one, expressing the intent to say without showing, involves lexical, pointing and fingerspelling units. We situate our descriptive concepts with respect to those used by SL linguists who, like us, adopt a cognitive-functionalist approach. To this end, we expose a specific theoretical foundation of our approach, namely the termed "enunciation theories". The concept of "enunciation" is decisive in understanding the role of the gaze both in anchoring of deixis and in referential tracking in SL discourse. It entails the opposition between "Enunciation” and "Utterance” Domains. The first links the signer/speaker and his/her addressee, establishing them by the very ‘act of enunciation’ as 1st and 2nd person. The second is internal to the discourse produced. From this perspective, using examples from corpora of narratives in twelve SLs, we illustrate the crucial role of the gaze in the creation and tracking of reference, in that it signals both the signer's intent and the passage from one intention to another. In SL discourse, reference is provided either by lexical or transfer units, mainly depending of its status of activation. Crosslinguistic analysis shows many structural similarities between SLs, notably that animate entities are typically introduced by a lexical unit but re-introduced through various transfer units.